2007
DOI: 10.1158/1078-0432.ccr-06-2705
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mitotic Segregation Errors Mediate Chromosomal Instability in Aggressive Urothelial Cancers

Abstract: Purpose: Chromosomal instability (CIN) is believed to have an important role in the pathogenesis of urothelial cancer (UC).The aim of this study was to evaluate whether disturbances of mitotic segregation contribute to CIN in UC, if these processes have any effect on the course of disease, and how deregulation of these mechanisms affects tumor cell growth. Experimental Design: We developed molecular cytogenetic methods to classify mitotic segregation abnormalities in a panel of UC cell lines. Mitotic instabili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…Hence, the results suggest that a major difference between MS1 and MS2 tumors is that the latter are more likely to have passed through a phase of genomic instability, augmented in the presence of TP53 impairment. This is in line with the finding that the presence of aberrant mitoses in pathologic slides of urothelial carcinoma is associated with a poor prognosis (47). The near absence of FGA in MS1 tumors with TP53/MDM2 mutations and the significantly higher number of FGA in MS2 TP53/MDM2wt cases suggests that the critical event separating MS1 tumors from MS2 tumors is a preceding phase of genomic instability and not the impairment of TP53 activity per se.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, the results suggest that a major difference between MS1 and MS2 tumors is that the latter are more likely to have passed through a phase of genomic instability, augmented in the presence of TP53 impairment. This is in line with the finding that the presence of aberrant mitoses in pathologic slides of urothelial carcinoma is associated with a poor prognosis (47). The near absence of FGA in MS1 tumors with TP53/MDM2 mutations and the significantly higher number of FGA in MS2 TP53/MDM2wt cases suggests that the critical event separating MS1 tumors from MS2 tumors is a preceding phase of genomic instability and not the impairment of TP53 activity per se.…”
Section: Discussionsupporting
confidence: 87%
“…Cell culture, harvest, and chromosome preparation for banding and fluorescence in situ hybridization (FISH) were according to standard methods (26). For analysis of chromosome dynamics at mitosis in tissue cultures, cells were harvested without metaphase arrest and stained with H&E. Anaphase cells and metaphase cells were scored in each case with AB and MM as defined by Jin et al (27).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, several recent studies have indicated that a high rate of such errors may be an adverse prognostic marker in several types of tumours (Yamamoto et al 2006;Jin et al 2007;Stewénius et al 2007) and that disturbances of chromosome segregation may be an early event in carcinogenesis (Meeker et al 2004). Hansemann described three types of chromosome segregation errors in tumour tissue sections (Hansemann 1891): anaphase bridges, multipolar mitoses, and asymmetrical bipolar mitoses.…”
Section: Introductionmentioning
confidence: 99%